Intra-Operative and Post-Operative Common Complications of Hysterectomy - Marriam Ashraf, Laiba Zahid, Farooq Ahmad, Muhammad Yousaf, Saba Naseem, Ghulam Mohi Ud Din, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The most prevalent gynaecological surgeries in the US is the hysterectomy. With more than 600,000 procedures carried out year. This study aims to find intra-operative and post-operative common complications of hysterectomy. Methods: A study conducted that was cross-sectional in the Unit 1 Gynecological Department Services Hospital in Lahore. The purposive sampling technique was applied to collect data. Total 120 gynecologist’s participants were investigated during this research. The target demographic was between the ages of 25 and 50. Consultants, PGRs, and SRs completed the questionnaire. The information gathered was written down, compared, and then examined. Results: According to the findings of this study, the most common intra-operative complication of hysterectomy is bowel injury (16.7%), followed by genitourinary (GU) and gastrointestinal (GI) tract injury (0.8%). The most prevalent post-operative complication was anuria (19.2%). Pulmonary Embolism (Bronchitis, Pulmonary Collapse) was responsible for 8% of the problems, whereas Hematoma Formation was responsible for 19.2%. Practical implication: The research on the common complications hysterectomy in the intra and post operative settings will allow for us to plan interventions in accordance to these complications which will better the medical intervention procedure and add to the literature of the subject. Conclusion: It is clear that the most common intra-operative complication of hysterectomy is Bowel Injury, the most common post-operative complication is Anuria. Keywords: Hysterectomy, Abdominal hysterectomy, vaginal hysterectomy, Intra-operative complications, Post-operative complications, surgical procedures, operating room.